(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Critical review of classification of weed vegetation of crops cultures of the Crimea is presented. It includes 19 associations, 8 alliances, 4 orders of class Stellarietea mediae according to Braun-Blanquet system. Phytocoenological characteristic of syntaxons, their diagnostical species have been revealed. The features of zonal distributional of communities in various agrocoenoses are considered.